Dampak Program Bina Keluarga Balita (BKB) Terhadap Tumbuh Kembang Anak Balita 6-24 Bulan (The Impact Of Bina Keluarga Balita (BKB) Program To The Growth Development Of Toddler 6-24 Months) - Andri Wahyuni; Sulistiyani Sulistiyani; Leersia Yusi Ratnawati (Pustaka Kesehatan, 2014)
The growth development is two difference phenomenons, but it is related and difficult to separated, that is growth and development. Bina Keluarga Balita (BKB) Program is one of the Keluarga Berencana (KB) program which purpose is to increase the knowledge and skills of parents and other family members to build the growth development of toddler by their ages. The aim of this study is to analyze the impact of Bina Keluarga Balita (BKB) program to the growth development toddler 6-24 months in the working area of Sumbersari subdistrict of Jember. The research type was observational analytic with cohort approaches. The samples about 130 toddlers (65 toddlers who family is participate and not participate on BKB) taken by Proportional Random Sampling. Based on Chi-Square results of statistical tests, it’s known that the difference of parenting nutrition, love pattern, teach pattern, and growth development between toddler 6-24 months who family is participate and not participate on BKB with the Sig or p = 0.0001 (p<α).   Keywords: Bina Keluarga Balita Program, Growth Development Of Toddler, 6-24 Months